Does household help prevent loneliness among the elderly? An evaluation of a policy reform in the Netherlands - Jelena Arsenijevic; Wim Groot (BMC, 2018)
Abstract Background Household help is a community intervention in the Netherlands. Its primary goal is to provide professional help in doing domestic work. A secondary goal of the intervention is to alleviate loneliness. In 2007, a major health care reform and budget cut changed household help. After the reform alleviating loneliness is no longer an aim of the intervention. In this study we evaluate the effects of the policy change in household help on loneliness among older adults in the Netherlands. Methods We use SHARE data collected during the period 2004-2013 to compare levels of loneliness among older adults in the Netherlands and those in 9 other European countries (Austria, Belgium, Germany, Denmark, Italy, France, Sweden, Spain and Switzerland). We use a synthetic control method (SCM) based on aggregate data. To check the robustness of our results we also apply a difference-in-differences (DiD) estimator that allows us to estimate the effects of policy changes using individual level data. Results In 2004, the prevalence of loneliness ranged between 6.5% in the Netherlands and 15.4% in Italy. Loneliness increased with time for all observed countries. The increase between 2004 and 2013 was highest in France − 30.2%, Italy - 33. 4% and Belgium - 25.0%. The level of loneliness among older adults in the Netherlands increased after 2011. However, it is still lower than in other countries. There was no statistical significant difference in age between waves (67.36 ± 13.7 before 2011 to 68.55 ± 9.24 after 2011, p = 0.01). Based on the DiD estimator, there is no statistically significant difference in the incidence of loneliness between older adults in the Netherlands and those in the control countries. Conclusion Our results do not suggest that the policy change and budget cut in 2007 on household help has had an effect on loneliness. In absolute numbers, the prevalence of loneliness has increased since 2011, however we find no evidence that this can be attributed to the policy change.